2006
DOI: 10.1074/mcp.m500262-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Antioxidant Proteins in Dendritic Cells

Abstract: Dendritic cells (DCs) display the unique ability to activate naive T cells and to initiate primary T cell responses revealed in DC-T cell alloreactions. DCs frequently operate under stress conditions. Oxidative stress enhances the production of inflammatory cytokines by DCs. We performed a proteomic analysis to see which major changes occur, at the protein expression level, during DC differentiation and maturation. Comparative two-dimensional gel analysis of the monocyte, immature DC, and mature DC stages was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 78 publications
8
31
0
Order By: Relevance
“…Consequently, it can be deduced that during DC differentiation process, taking place in 6-days culture, large increase in the concentration of mitochondrial proteins, such as MnSOD, can occur from marginal increase of the corresponding mRNA levels (Angenieux et al, 2001). Overall, these findings confirmed previous observations (Rivollier et al, 2006) showing that DC are equipped with a very efficient anti-oxidant systems that may assure higher resistance to oxidative environments.…”
Section: Resultssupporting
confidence: 84%
“…Consequently, it can be deduced that during DC differentiation process, taking place in 6-days culture, large increase in the concentration of mitochondrial proteins, such as MnSOD, can occur from marginal increase of the corresponding mRNA levels (Angenieux et al, 2001). Overall, these findings confirmed previous observations (Rivollier et al, 2006) showing that DC are equipped with a very efficient anti-oxidant systems that may assure higher resistance to oxidative environments.…”
Section: Resultssupporting
confidence: 84%
“…In the same study, a high induction of multiple electrophoretic forms of SOD2 during the maturation process of DCs was described, confirming earlier findings by Rivollier et al [65]. The latter study investigated the relation between oxidative stress protein expression profiles and DC differentiation and maturation, making use of 2-DE and MALDI-TOF/TOF-MS. Not only SOD2 was highly expressed in i-and mDCs as compared to monocytes, but also two other important oxidative stress proteins, Prx1 and thioredoxin 1 (Trx1), involved in several cellular redox processes.…”
Section: Studies On Complete Cell Lysates From Dcssupporting
confidence: 74%
“…Most of these studies were performed using micro-array analysis and are reviewed elsewhere [54][55][56][57][58][59][60][61][62][63][64][65][66]. With the advent of proteomic approaches, also studies on DCs have been performed at the protein level, resulting in the identification of different proteins that add new information and are complementary to those obtained at the mRNA level.…”
Section: Maturation Process Of Human Dcsmentioning
confidence: 99%
“…In addition, our data reveal that mDCs convey protection against oxidants by increasing thiol expression in lymphocytes by an as yet undefined mechanism. It should be pointed out, however, that recent proteomic-based analyses have revealed that several antioxidative proteins are up-regulated as MPs differentiate into mDCs (34), and multiple mechanisms are therefore likely to contribute to the observed mDC-mediated lymphocyte protection.…”
Section: Resultsmentioning
confidence: 99%